Health care provision for refugees in Germany - one-year evaluation of an outpatient clinic in an urban emergency accommodation - Hannah S. Borgschulte; Gerhard A. Wiesmüller; Anne Bunte; Florian Neuhann (BMC, 2018)
Abstract Background In 2015, Germany recorded the highest rates of refugees since the early 1990s. Access to medical care is a legally regulated fundamental element of aid for refugees. In practice, there are several hurdles such as language barriers and legal regulations. In response to the massively increased need, special outpatient services for refugees were started in several German cities. In Cologne, an outpatient clinic (OPD) was established in the largest emergency accommodation centre for refugees supported by the Cologne municipality and operated by the German Red Cross and physicians from the Association of Statutory Health Insurance Physicians. This study reports experiences of the first year of the OPD regarding structure, processes and utilization. Methods Employing mixed methods, between May and December 2015 cross sectional pseudonymized data from patients' contacts were collected, coded in the International Classification of Primary Care (ICPC) and evaluated. Infrastructure, equipment, process organisation and function of the OPD were assessed during five participatory observations and triangulated with results of a self-administered questionnaire for staff and four qualitative interviews with key informants. Results During the observation period a total of 2205 persons (67% male) stayed in the emergency accommodation and 984 patient contacts (51% male) were registered, mainly by young persons from Western Balkan countries and Syria. Medical treatment was sought primarily for acute respiratory-, loco-motor-system- and skin symptoms followed by chronic physical diseases. Headache, back and neck pain and acute respiratory infection were the most frequent diagnoses. Questionnaires and interviews among staff revealed language barriers and psycho-trauma as the most frequently reported challenges. Equipment and staffing was adequate, but patient documentation was not systematic, leading to loss of information. Conclusion To facilitate refugees' appropriate access to health care, the OPD was seen as functional for this refugee accommodation centre. Need was recognised for standardized, data protective documentation and a health passport for clients for medical information. Psychological support for refugees needs expansion taking legal circumstances and coverage of costs into consideration. To improve patient communication employees working with refugees should be offered an introduction to culturally sensitive understanding of health and illness.